Radar Observation of Extreme Vertical Drafts in the Polar Summer Mesosphere. Issue 16 (16th August 2021) - Chau, J. L.; Marino, R.; Feraco, F.; Urco, J. M.; Baumgarten, G.; Lübken, F.‐J.; Hocking, W. K.; Schult, C.; Renkwitz, T.; Latteck, R.
Abstract: The polar summer mesosphere is the Earth's coldest region, allowing the formation of mesospheric ice clouds. These ice clouds produce strong polar mesospheric summer echoes (PMSE) that are used as tracers of mesospheric dynamics. Here, we report the first observations of extreme vertical drafts ( ± 50 m s − 1 ) in the mesosphere obtained from PMSE, characterized by velocities more than five standard deviations larger than the observed vertical wind variability. Using aperture synthesis radar imaging, the observed PMSE morphology resembles a solitary wave in a varicose mode, narrow along propagation (3–4 km) and elongated ( > 10 km) transverse to propagation direction, with a relatively large vertical extent ( ∼ 13 km). These spatial features are similar to previously observed mesospheric bores, but we observe only one crest with much larger vertical extent and higher vertical velocities. Plain Language Summary: Extreme events are ubiquitous in geophysical flows. Examples of these events are tornadoes and rogue waves in the lower atmosphere and oceans, respectively. In the mesosphere, the boundary of Earth's atmosphere and outer space, extreme events can also occur, although this region is poorly observed. Here, we present the first observations of extreme vertical velocities ( ± 50 m s − 1 ) in the mesosphere, that are more than five times their expected standard deviation. These observations are possible by tracking and imaging strong mesospheric radar echoes that occur in the summer at polar latitudes, with a radar used in a radio camera mode. The morphology of our observations resembles previously observed instabilities called bores or wave walls, but with much larger vertical velocities and vertical extents. Key Points: First observations of extreme vertical velocities in the polar summer mesosphere The observed solitary wave in a varicose mode resembles a mesospheric bore, with large vertical extent and vertical velocities Such extreme events might have been missed or ignored in previous observations of vertical velocities or other mesospheric observations